Representasi Perempuan dalam Industri Sinema - Rahmat Edi Irawan (Bina Nusantara University, 2014)
Studies on the presence and the role of women in film industry are interesting to observe. Physically, women exist and play role in the world of film industry, as old as the film itself. In terms of quantity, the number of women seen on screen is also not inferior to men seen in the film. The issue is precisely whether the presence and nearly with the same quantity with men, women are enough to give meaning to the quality of the film itself. Article used literature study, to see how the literatures interrelate several theories of mass communication, especially those raised on the issue of representation. Conclusions or results of the study for this paper are women’s presence and participation as well as comparable quantity of them with men in film industry do not have a lot contribution to the improvement of the quality of the film industry itself. This relates to the women who exist and participate in the film industry rely only on certain physical size of the body and woman is only as a complement to sweeten the mere presence of a movie.